The computational fluid dynamics analysis using vortex particle method - Anaphat Manovachirasan; Pennung Warnitchai; Kim, Kidu; Punchet Thammarak; Park, Kyung Ho; Thanakorn Pheeraphan; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
This study considers a Computational Fluid Dynamics Analysis using Vortex Particle method by C++ programming. Circular, triangular and square sections are performing to be the numerical examples for program validation. Inviscid flow which is an ideal flow is used to be the incoming flow. The expectation result of this study is drag coefficient, lift coefficient and strouhal number. Results have shown that the drag coefficient has percent difference between experiment data and result about 10-15 percent for circular and triangular section, only square section has 3 3 percent. Moreover, strouhal number has around 15 percent difference for all three sections when compare to the experiment data. This program is the staiting point of the bridge section analysis. It can be developed more in conditions of viscous flow and vortex diffusion. Moreover, it can be developed the analytical speed such as Particle remeshing, Vortex release algorithm, Particle-Particle-Particle Mesh algorithm and so on. Keywords: Conputational Fluid Dynamics Analysis, Vortex Particle Method, Inviscid flow, Drag coefficient, Lift coefficient, Strouhal number.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2011
Keywords: Fluid dynamics; Vortex-motion